MANAGEMENT OF GUIDANCE AND COUNSELING SERVICES FOR EDUCATIONAL IMPROVEMENT IN SECONDARY SCHOOLS - Muhammad Misbahul Afandi; Aninda Sandhi Putri; Tarso Tarso; Deny Hadi Siswanto; Adian Purwo Nugroho (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
This study aims to describe the management of guidance and counseling (GC) services in improving the quality of education at SMA Muhammadiyah Mlati. A qualitative approach with a case study design was employed. Data were collected through in-depth interviews with guidance counselors, school principal, and homeroom teachers, as well as direct observations of GC service implementation and documentation analysis. The findings reveal that service planning is carried out systematically through the identification of student needs personal, social, academic, and career aspects. The organization of services includes task distribution based on counselor competencies, the establishment of working structure, and interdepartmental coordination within school. Service implementation is conducted by professionals with academic backgrounds in guidance and counseling, employing various active methods such as classical and modeling approaches. The types of services provided include informational, orientation, individual, group, responsive, and peer counseling. Evaluation is conducted regularly through the development of instruments, data collection, and result analysis, as well as the identification of supporting and inhibiting factors. The study found that GC services are effective and positively received by students. It concludes that well-planned, organized, and collaborative management of GC services can significantly contribute to enhancing quality of education at the secondary school level